Youth Leadership Readiness for Golden Indonesia 2045: A Qualitative Literature-Based Framework for Democratic Governance and Public Sector Transformation - Anggita Meylinda (Universitas Muhammadiyah Jakarta, 2024)
Indonesia’s aspiration to achieve the Golden Indonesia 2045 vision depends not only on economic growth and demographic advantage, but also on the quality of leadership that will guide public institutions, political processes, and social transformation in the coming decades. As Indonesia approaches the centennial of its independence, the country is expected to benefit from a large productive-age population. However, demographic advantage does not automatically produce national progress. It must be converted into human capital, civic competence, institutional trust, and leadership capacity. This article examines how the younger generation can be prepared as future leaders for Golden Indonesia 2045. Using a qualitative literature-based method, this study synthesises academic literature, policy documents, and conceptual perspectives on youth leadership, political participation, demographic dividend, digital governance, and public sector transformation. The findings indicate that youth leadership readiness requires more than generational replacement. It demands the development of agile, ethical, participatory, innovative, and digitally adaptive leadership capabilities. This article proposes the ADAPTIVE Youth Leadership Framework, consisting of agile governance orientation, democratic participation, accountability and integrity, policy innovation, technological literacy, inclusive collaboration, visionary resilience, and ethical public value creation. The study concludes that youth participation in politics and public governance must be institutionally supported through leadership education, civic engagement platforms, intergenerational collaboration, digital governance mechanisms, and transparent recruitment into strategic public roles. The article contributes to public administration and political leadership studies by linking demographic dividend discourse with youth leadership capacity and democratic governance transformation in Indonesia.